2015
DOI: 10.1177/0309133314567582
|View full text |Cite
|
Sign up to set email alerts
|

The Coyote-Proof Pasture Experiment

Abstract: Few scientific experiments have influenced more land than one conducted in the Wallowa Mountains of eastern Oregon by the US Department of Agriculture’s Bureau of Plant Industry and US Forest Service in 1907–1909. Four square miles of land were enclosed with a “coyote-proof fence,” guarded by a hunter, and stocked with an untended band of sheep. Data were collected on vegetation and sheep performance inside and outside the fence, and two years later success was declared. By 1910, the Forest Service had wrested… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…Similarly, Ockenfels et al (1997) found that fenced roads significantly constrain the shapes of pronghorn home range. At a broader scale, fence construction across the American West (Sayre, 2015) could shape the geographic distribution of pronghorn, confining them to a portion of their historical range. Pronghorn also exhibited larger seasonal variations in fence behaviours than mule deer, encountering fences 1.5 times more in summer than in winter.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, Ockenfels et al (1997) found that fenced roads significantly constrain the shapes of pronghorn home range. At a broader scale, fence construction across the American West (Sayre, 2015) could shape the geographic distribution of pronghorn, confining them to a portion of their historical range. Pronghorn also exhibited larger seasonal variations in fence behaviours than mule deer, encountering fences 1.5 times more in summer than in winter.…”
Section: Discussionmentioning
confidence: 99%
“…To investigate these two species' behavioural responses to fences, we developed and applied a repeatable method that categorizes individual movement behaviours in response to linear barriers such as fences (Barrier Behaviour Analysis, BaBA). We conducted this work in western Wyoming, USA—a region known for some of the longest remaining ungulate migrations in North America and where fencing is a ubiquitous landscape feature (Middleton et al., 2020; Sayre, 2015). We identify extensive, complex behavioural responses of these wildlife to fences, examine spatial and temporal characteristics of these responses and demonstrate how BaBA might be used to inform conservation efforts.…”
Section: Introductionmentioning
confidence: 99%